Inclusão social de alunos com necessidades educacionais especiais em contexto escolar por atores sociais da escola - Silva, Daniele Aparecida da (2009)
The inclusion of students with special educational needs in the regular education system represents a viable alternative for social inclusion of this population segment which is historically excluded of its rights as citizens. However the real conditions faced by those who defend and act supporting the proposal of the social inclusion are well known. Objective: The purpose of this study is to analyse the meanings of social inclusion of students with special educational needs in school´s daily life, by the social actors that belongs to the institution. Methodology: A field research has been done, the etnographic type of it, with participating observation and semi-structured interviews at a regular school of fundamental education, located in Joao Pessoa, state of Paraiba, Brazil. The adopted criteria for the school picking was the highest number of enrolled students with special educational needs compared to other schools in the same city. Ninetynine social actors participated in the research, besides fifteen students with special educational needs, fifty-five students without it, ten teachers and nineteen employees of school administrative staff. For data analysis the theme content analysis in lexical and contextual basis was used with support of the ALCESTE system for textual data analysis. Results: The analysis points towards four meanings for the social inclusion of students with special educational needs studied through participating observation in the context of school with teachers and administrative staff: Right to Regular Education-33.33%; Educational Planning and Inclusion-29.17%; What´s Social Exclusion/Inclusion?-16.67%; Commitment: School and Family-20.83%. The meanings of inclusion for students with special educational needs obtained by semi-structured interviews with the special needs students themselves made arise six meanings: the larger percentage was Ethic-Political Suffering (33.33%), followed by Preservation of Oneself (19.44%), Me and the Other (16.67%) in third place, Good and Bad Meetings: Approximation and Removal (11.11%), in fourth place; Equality and Difference (10.19%), in fifth place; Normal Child who studies and Play (9.26%) finally. As for the students without special educational needs, using the semi-structured interviews, the obtained meanings for inclusion of students with special needs were: Equality and Difference (72.29%), followed by Child who studies and Play (11.75%), Family and Daily Life (8.73%) and Exclusion by Poverty (7.23%). We conclude that the meanings for inclusion of students with special educational needs pose as indicators for continuous thinking on what inclusion means in educational contexts, shown by those who experience this situation in the most varied forms in daily life.